Stepping Towards Economic Independence through Agricultural Tourism and Cultural Preservation in Pantai Labu District - Lubis, Adelina; Effendi , Effendi Ihsan; Kuswardani , Retna Astuti; Siregar , Muhammad Akbar (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Pantai Labu District in Deli Serdang Regency, North Sumatra, has high agricultural and cultural tourism potential. However, this potential has not been utilized optimally by the local community. This results in low levels of income and economic independence in the community. This community service activity aims to increase the economic independence of the community through the development of agricultural tourism and cultural preservation in Pantai Labu District. This activity is carried out using several methods, namely: (a) Socialization and training to the community regarding the development of agricultural tourism and cultural preservation. (b) Assistance in forming tourism awareness groups (pokdarwis). (c) Development of tourist infrastructure. (d) Promotion of tourism through various media.(e) This activity produced several results, namely: (a) Increasing community knowledge and skills regarding the development of agricultural tourism and cultural preservation. (b) Formation of pokdarwis in several villages in Pantai Labu District. (c) Improved tourist infrastructure in several locations. (d) The increasing number of tourists visiting Labu Beach District. This community service activity shows that the development of agricultural tourism and cultural preservation can increase the economic independence of the community in Pantai Labu District.